The role of modern technologies and platforms in the effective teaching of foreign languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The role of modern technologies and platforms in the effective teaching of foreign languages is increasingly recognized as a critical factor in enhancing language acquisition. This study explores how technological advancements such as language learning apps, online platforms, and interactive tools contribute to more engaging and efficient language education. By examining various applications and their impacts on learners, the research aims to highlight best practices and future directions for integrating technology into language teaching.